TANTANGAN IMPLEMENTASI PEMBELAJARAN INOVATIF DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Hanipah, Siti; Naila Salsabila, Zahra; Sabila; Nurmala Sari, Elsa; Dwiprabowo, Risky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes challenges in implementing innovative learning within the Merdeka Curriculum at SD Negeri Tugu 3 Cimanggis, Depok. The curriculum emphasizes student-centered, project-based learning, differentiation, and strengthening the Pancasila Student Profile (P5). Using a descriptive qualitative approach through observation, interviews, and document analysis, the research found obstacles such as uneven student participation, limited digital facilities, restricted learning spaces, and varied teacher technological competence. Adaptive strategies emerged, including simple media use, rotating digital access, teacher collaboration, and active principal supervision. The study concludes that equitable resources and continuous teacher training are essential to optimize innovative learning.